Using the Medical Model in Education : Can pills make you clever?. - Turner, David A. (Bloomsbury Publishing, 2009)
David Turner examines commonly held beliefs about learning, knowledge and intelligence, and critically assesses claims that certain drugs can improve learning and memory.